Compounds purified from edible fungi fight against chronic inflammation through oxidative stress regulation - Xia, Yidan; Wang, Dongxu; Li, Jiaqi; Chen, Minqi; Wang, Duo; Jiang, Ziping; Liu, Bin (Frontiers in Pharmacology, 2022)
Chronic inflammation is associated with various chronic diseases, including cardiovascular disease, neurodegenerative disease and cancer, which severely affect the health and quality of life of people. Oxidative stress-induced by unbalanced production and elimination of reactive oxygen species (ROS) is regarded as one of the essential factors causing chronic inflammation. In recent years, the antioxidant effects of natural compounds have been reported to have more advantages than synthetic antioxidants. Of which, the studies of mushrooms have received considerable attention. Mushrooms have been consumed by humans as precious nourishment for 3000 years, and so far, more than 350 types have been identified in China. Mushrooms are rich in polysaccharides, peptides, polyphenols, alkaloids, and terpenoids, and are associated with several healthy biological functions, especially antioxidant properties. Extracts purified from mushrooms can activate the expression of antioxidant enzymes through the Keap1/Nrf2/ARE pathway to neutralize excessive ROS and inhibit chronic inflammation caused by ROS through the NF-κB pathway. Recently, the antioxidant properties of mushrooms have been successfully applied in treating cardiovascular disease (CAD), neurodegenerative diseases, and cancer. The present review summarizes the antioxidant properties and mechanisms of compounds purified from mushrooms. Furthermore, it emphasizes the oxidative stress regulation of mushrooms to fight against chronic inflammation.